(untitled) (Iraqi Journal of Medical Sciences, 2019)
Ganglion is defined a cystic lesion composed of myxoid matrix having jelly like consistency and is lined by pseudomembrane. Large ganglionic cyst in Hoffa Pad is quite uncommon and only few are mentioned in literatures. A 25-year old female presented with history of gradually worsening anterior knee pain and swelling for 10 months duration, she was disabled due to repeated attacks of knee pain. Magnetic resonance imaging (MRI) shows large intra-articular multilocular cyst. The decision was to do open excision of the cyst in order to decrease the recurrence rate. Histopathological finding shows multi-lobulated cysts with glassy fibrous wall and clear jelly like consistency, which confirm diagnosis. Postoperative period was uneventful and she was doing well during follow up after four months. Large ganglionic cyst developed in Hoffa fat pad of the knee should be considered in deferential diagnosis of intraarticular mass causing pain around the knee. The decision was open excision depending on MRI finding to avoid incomplete resection and prevent recurrence. Keywords:Knee, Ganglion Cyst, Hoffa Fat Pad, MRI Citation:Dagher AE, Hasan FK. Large Intraarticular Ganglion in Knee Joint: A case report. Iraqi JMS. 2019; 17(2): 161-165. doi: 10.22578/IJMS.17.2.10